2014
DOI: 10.1002/ase.1478
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based decision about test scoring rules in clinical anatomy multiple‐choice examinations

Abstract: In theory the formula scoring methods increase the reliability of multiple-choice tests in comparison with number-right scoring. This study aimed to evaluate the impact of the formula scoring method in clinical anatomy multiple-choice examinations, and to compare it with that from the number-right scoring method, hoping to achieve an evidence-based decision about test scoring rules. Two hundred and ninety-eight students completed an examination in clinical anatomy which included 40 multiple-choice questions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…MCQs have many merits and can produce meaningful assessment of knowledge, though their validity can suffer for many reasons (Vahalia et al, ; Downing, ). Severo et al () found a significant effect on the calculation of student marks when a formula scoring method instead of a number scoring method was used. They conclude that use of the formula scoring method rewards students who have partial knowledge, as opposed to those who have partial misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…MCQs have many merits and can produce meaningful assessment of knowledge, though their validity can suffer for many reasons (Vahalia et al, ; Downing, ). Severo et al () found a significant effect on the calculation of student marks when a formula scoring method instead of a number scoring method was used. They conclude that use of the formula scoring method rewards students who have partial knowledge, as opposed to those who have partial misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…The above arguments provide a strong rationale for incorporating EBA into anatomy education. Medical education curricula in many countries have either incorporated EBA into their anatomy education programs or are in the process of doing so (Severo et al, 2015). Nevertheless, there are countries/regions in which EBA is still viewed through the prism of clinical practice and anatomy education continues as a non-evidence-based exercise (Kumar & Singh, 2020).…”
Section: Interpretation Of Evidence-based Anatomy In the Present Daymentioning
confidence: 99%